Delineation of terrestrial and marine productivity in the southwestern continental margin of India. (1st June 2022) - Srivastava, Jyoti; Manoj, M.C.; Manjunatha, B.R.; Yoganandan, V.; Jose, Jithin; Balakrishna, K; Naveen Kumar, A.; Ahmed, Aarif
Highlights: Terrestrial/marine paleoproductivity proxies show paleosummer monsoon fluctuations. Pollen is more reliable and coherent climate proxy than marine ones. Summer monsoon weakened along SW India during Younger Dryas. Monsoon intensified from early to late Holocene with a break during 6.7–4.0 ka. Abstract: Although there are numerous investigations on the reconstruction of palaeomonsoon, there are inconsistencies between the terrestrial and marine archives. In this study, we have made an attempt to unravel this problem from a multi-proxy study of a sediment core from the south-west continental margin of India (SWCI). Here, we characterize pollen and dinocyst, and compare it with the marine primary productivity indicators (organic carbon and CaCO3 ) in an AMS 14 C-dated sediment core collected off the SWCI. The sedimentation rate decreases consistently from late-glacial through early Holocene to the late Holocene (31.16 cm/ka, 24.8 cm/ka and 15.4 cm/ka respectively). The down-core distribution of pollen shows the presence of Poaceae and Cyperaceae without mangroves and other terrestrial pollen around 13.2 ka BP − 11.7 ka BP, suggesting a weakened summer monsoon during the Younger Dryas. Increase in the abundance of mangroves and tropical moist/dry deciduous forest pollen along with the dinocyst during ∼ 11.7 ka to 8.5 ka BP indicates the growth of vegetation in the hinterland as a result of the intensification of monsoon during the early Holocene. This was followed by a maximum marine transgression phase along with a strengthened summer monsoon between ∼ 8.0 ka BP and 6.7 ka BP, as evidenced by the dominance of mangroves and presence of terrestrial pollen taxa. Further, a significant decline of vegetation during 6.7 ka BP to 4.0 ka BP indicates weakened summer monsoon. In contrast to the pollen profiles, however, a significant increase in the mangroves and herbaceous pollen from 4.0 ka BP to 3.2 ka BP suggests a gradual revival of the summer monsoon during the late Holocene. Above mentioned paleoclimatic reconstructions are in contrast to the marine CaCO3  and organic carbon, as these are lower and fairly constant from Younger Dryas upto 8.0 ka BP, then gradually increased till 6.5 ka BP, and show little variations during the late Holocene. This study suggests that the pollen preserved in the marine sediments are not only reliable indicators, but they are also consistent with other palaeomonsoon proxies measured in archives from the South Asia for the reconstruction of climate.